Construction and system evolution analysis of China’s food security indicator system - Yuting, Zhao; Meng, Qu (Frontiers in Sustainable Food Systems, 2024)
In this paper, we use qualitative and quantitative methods to determine the food security indicator system and observe the development of China's food security from 1961 to 2019 to provide a reference for countr ies threatened by hunger and malnutrition to get out of the predicament. First, 199 pieces of literature were subjected to three-level coding and saturation test using Nvivo software to preliminarily establi sh an indicator system for measuring China's food security, which consists of two categories: food ch ain and external environment, five subsystems: food supply, food circulation, food consumption, inte rnational factors, and domestic factors, as well as 12 specific indicators. Subsequently, the entropy w eight coefficient and hierarchical analysis methods are used to calculate two different indicator weigh ts. Monte Carlo simulation compares the uncertainty of the indicator weights calculated by the two m ethods. We found that the uncertainty of the indicator weights determined by the hierarchical analysis method is much higher than that of the entropy coefficient method, so the indicator weights determin ed by the entropy coefficient method are chosen. Based on the formation of the food security indicato r system, the obstacle degree test was carried out for each indicator. We found that the average wage of urban employees before 2015 was the main obstacle to China's food security. However, the popula tion kept growing after 2015, which became the main obstacle to China's food security. Secondly, the evolution characteristics of the overall level of China's food security and the subsystems from 1961 t o 2019 were analyzed individually. We found that the overall level of China's food security has been continuously improving. However, the subsystems still have hidden dangers, and the most prominent one is the food consumption subsystem, whose composite index has been continuously decreasing an d has become the main factor undermining China's food security. The scientific construction of China 's food security indicator system will help to identify and warn of hidden food security problems pro mptly and, at the same time, will help to summarize and promote China's successful experience in saf eguarding food security.